Hybrid and/or mixed infection by pig and human Ascaris in a Guarani indigenous village in southern Brazil. - Veridiana Lenartovicz Boeira; Renata Coltro Bezagio; Marina Silva de Carvalho; Rinaldo Ferreira Gandra; Ana Paula de Abreu; Cristiano Lara Massara; Cristiane Maria Colli; Max Jean de Ornelas Toledo (PLoS Neglected Tropical Diseases)
Background Ascaris lumbricoides and Ascaris suum are nematode parasites that infect millions of people and pigs worldwide, respectively. Reports of cross-infection and hybridization between the two species has stimulated molecular epidemiological studies of the Ascaris genus. In this study, we evaluated the dynamics of Ascaris transmission between Guarani indigenous schoolchildren, pigs, and the environment of a village in the state of Paraná, southern Brazil. Methodology/principal findings Parasitological and molecular analyses of fecal samples from humans and pigs, and soil samples from the village were carried out. Eggs of Ascaris spp. were observed in 8.4% (7/83) of human samples, 44.4% (8/18) of pig samples, and 8.9% (6/68) of soil samples. PCR amplification of the ITS-1 locus of the rDNA gene in samples that were positive in the parasitological examination revealed mixed infection and/or hybrids of the two species, A. lumbricoides and A. suum, in human and swine hosts. The soil, which was contaminated by both human and swine feces, also contained eggs of the two Ascaris species and hybrids, thus constituting a source of Ascaris infection for both hosts. DNA from A. lumbricoides and A. suum, individually, was detected in samples from humans and pigs, respectively, and the soil, while DNA from hybrid and/or Ascaris spp. was detected in samples from both hosts and the soil. Conclusions/significance The results of this study confirm the necessity of a One Health approach with the correct disposal of both human and animal feces to control the spread of human and swine ascariasis.